Current Problems of Rhinosurgery - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
If you breathe in through your mouth several times and inhale and exhale through your nose, you can feel that you are breathing through your mouth. But the apparent convenience has consequences. Breathing through the nose is important and necessary. Passing through the nasal cavity, the air undergoes mechanical cleaning from dust, allergens and pathogenic microorganisms. The air flow is also heated, which prevents cold air from entering the bronchopulmonary system. Up to 80% of the total number of patients who consult an otolaryngologist have problems with nasal breathing. It may depend on various factors and it is very important to understand that this problem requires the careful attention of the doctor and the patient. Difficulty in breathing through the nose not only makes it difficult to communicate, exercise and sleep, but can also lead to the development of inflammatory diseases in the sinuses and similar complications. Therefore, if you notice any warning signs, do not forget to consult a doctor. All problems can be solved!